The Juridical Analysis of the Process of Applying for Expired Building Use Rights in the Concept of Legal Certainty - Kusumabrata, Dhandy Armanda; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to find out and analyze the legal status of a deed of sale and purchase of building use rights as a condition for extending the term of building use rights that have expired. The approach method in this research is the approach to Legislative Regulations. The research specifications are analytical descriptive, the data required includes secondary data taken using qualitative analysis methods. The data analysis method uses deductive logic based on research. It is concluded that the Sale and Purchase Agreement in the form of a Sale and Purchase Agreement (PPJB) made before a Notary is invalid because the seller does not have the right to carry out a PPJB on land that is already controlled by the State or in other words Building Use Rights. has expired, so the PPJB that was made is null and void by law. Keywords: Agreement; Building; Expired.